Impact of Dietary Lead (Pb) on the Human Gastrointestinal Tract: A Review - Samsul, Erwin; Muzaqi, Muhammad Choirul; Yotam, Yotam; Putra, Mitosie Gunarsa Caesar; Mutiara, Nur Adinda; Gunawan, Jevon Ecclesia; Rahman, Muhammad Alif; Salsabila, Syifa Kamila (Journal of Pharmaceuticals and Natural Sciences, 2025)
Lead (Pb), a toxic heavy metal, frequently contaminates food and beverages due to environmental pollution and industrial processes. This study reviews lead's toxic effects on the human gastrointestinal tract through a narrative literature review from credible databases such as PubMed, Elsevier, and Google Scholar. Findings reveal that lead concentrations vary by food type, processing methods, and storage duration. For instance, lead levels in preserved eggs range from 334-1782 mg/kg, exceeding the safe limit (0.25 mg/kg), causing nausea, vomiting, and abdominal pain. Unwashed pears reached 18.5 mg/kg after 12 days, triggering similar symptoms. In contrast, grapes and vegetables showed low lead levels (<0.04 mg/kg) with no significant clinical effects. Food poisoning cases like contaminated candy in schools highlight the urgent need for strict monitoring. This review emphasizes strengthening food safety regulations, raising public awareness, and promoting further research to reduce exposure in the global food supply chain